Does Information Acquisition Influence the Adoption of Sustainable Land Management Practices? Evidence From Mpumalanga Province South Africa - Oduniyi, Oluwaseun Samuel; Tekana, Sibongile Sylvia (Frontiers in Sustainable Food Systems, 2021)
Agricultural information plays a vital role in adopting agricultural technology. The study explored if information acquisition is related to the adoption of sustainable land management practices (SLMP) and jointly decided in Mpumalanga Province of South Africa. Primary data were collected through face-to-face interviews, using a proportionate random sampling technique to get 250 smallholder farmers to participate in the survey. A seemingly unrelated bivariate probit (SUBP) model and a recursive bivariate probit (RBP) model were adopted to examine the objective. The statistical estimation of the SUBP showed that there is a relationship, an empirical association between information acquisition and SLMP; while RBP estimation showed that information acquisition was exogenous in the adoption model; thus, the decision to acquire information and adopt SLMP was not jointly decided. Therefore, the study presents the determinants of information acquisition alongside with the adoption of SLPM. The result from the SUBP model, indicated that the years spent in school; agricultural extension service; the number of extension visits and the years of farming, influenced both information acquisition and the adoption of SLMP. The cost attached positively influenced the adoption of SLMP; while gender, marital status and age only influenced the information acquisition.